Efektifitas Hipnoterapi Dalam Menurunkan Tingkat Kecemasan Pasien Gangguan Jiwa - Rahmah Putri Puspitasari; Wardatul Mufidah; Siti Nur Zunaidah (IDEA: Jurnal Psikologi, 2021)
The purpose of this study is to determine the effectiveness of hypnotherapy in decreasing anxiety levels in mental disorder patients.The hypothesis proposed is to find out whether hypnotherapy reduces the level of anxiety of mental disorder patients.The samples from this study involved 18 patients from Puskesmas II Denpasar Timur Bali.The sampling technique used in this study was Purposive Sampling. To obtain an anxiety score in this study, the method of data collection with observation, interview, hars psychology scale (Hamilton Anxiety Rating Scale) by testing anxiety scores using hypnosis therapy. The hypothesis test used is a paired samples statistical test. The results of the t-test analysis use paired sample test sign values. 2 tailed of : 0.002 and paired sample correlation value : 0.262 with mean pretest : 21.83 and mean post test : 18.44. with the conclusion of the value of the sig. the difference test gets a value of 0.000. The value is less than 0.05. This shows that there is a significant difference in the level of anxiety between before and after hypnotherapy, where there is a decrease in anxiety between before hypnosis and after hypnosis. So the proposed hypothesis is accepted. Key words : anxiety, hypnotherapy, mental disorder patient